2021
DOI: 10.3390/foods10010188
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic and Carotenoid Profile of Lamb’s Lettuce and Improvement of the Bioactive Content by Preharvest Conditions

Abstract: This study characterizes the phenolic, carotenoid and chlorophyll profile of lamb’s lettuce, a vegetable whose consumption in salads and ready-to-eat products is constantly growing. The MS/MS analysis allowed the identification of thirty-five phenolic compounds including hydroxybenzoic and hydroxycinnamic acids, flavanones, flavanols and flavanones, many of which are reported here in lamb’s lettuce for the first time. Chlorogenic acid was the principal phenolic compound found (57.1% of the total phenolic conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 81 publications
(105 reference statements)
2
11
0
Order By: Relevance
“…The commercial interest for corn salad has increased due to its leaves’ mild and delicate taste, and overall dietary characteristics and rich bioactive compound content [ 14 , 15 ]. Towards that end, the rosettes are known to contain several bioactive compounds, such as vitamin C, carotenoids, phenols, folic acid, sterols, and omega-3 fatty acids [ 16 , 17 , 18 , 19 ]. This commercial interest has encouraged producers around Europe to grow lamb’s lettuce on different scales, large or small, either in greenhouses or in open fields, and sell their produce to supermarkets and delicatessen restaurant supply chains [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The commercial interest for corn salad has increased due to its leaves’ mild and delicate taste, and overall dietary characteristics and rich bioactive compound content [ 14 , 15 ]. Towards that end, the rosettes are known to contain several bioactive compounds, such as vitamin C, carotenoids, phenols, folic acid, sterols, and omega-3 fatty acids [ 16 , 17 , 18 , 19 ]. This commercial interest has encouraged producers around Europe to grow lamb’s lettuce on different scales, large or small, either in greenhouses or in open fields, and sell their produce to supermarkets and delicatessen restaurant supply chains [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in lutein and β-carotene achieved in plants grown on the 50:50 mixtures was consistent with findings on lettuce by Kim et al (58) following increasing doses of soil amendment. In the same line, Hernández et al (85) suggested that reduced nitrogen availability resulted in reduced amounts of carotenoids, whereas high salinity induced the biosynthesis of these compounds. High amounts of carotenoids, such as lutein and β-carotene, may play a protective role against oxidative stress since they act as reactive oxygen species scavengers and quenchers of free radicals (11).…”
Section: Discussionmentioning
confidence: 94%
“…Chlorophyll and carotenoids were calculated by the absorbance method using a spectrophotometer (Shah, Houborg, and McCabe 2017), (Guberman-Pfeffer and Gascón 2018), (Hernández et al 2021). The chlorophyll test stages included, carefully weighing 0.5 g of the samples, addition of 10 mL of 100% methanol with a pipette, and then centrifuging at a speed of 4,500 rpm for 10 minutes.…”
Section: Chlorophyll and Carotenoidsmentioning
confidence: 99%